The Risk Stratification for Cervical Cancer and Precursors of Domestic HPV Testing With HPV 16/18 Genotyping in Women With NILM Cytology in CentralChina: A Cohort Study - Xu, Hui-Fang; Liu, Yin; Luo, Yan-Lin; Zhao, Dong-Mei; Jia, Man-Man; Chen, Pei-Pei; Li, Meng-Jie; Sun, Xing-Ai; Liu, Shu-Zheng; Sun, Xi-Bin; Zhang, Shao-Kai (Frontiers in Oncology, 2021)
Objective To evaluate the clinical performance and utility for risk stratification of DH3 HPV assay in women (≥30 years) with NILM cytology. Methods A prospective cohort was established in Central China between November 8 to December 14, 2016 which consisted of 2180 women aging 30-64 years with NILM cytology. At baseline, all women were screened using DH3 HPV assay. HPV 16/18 positive women would be assigned to colposcopy and biopsied if necessary. Then, hr-HPV positive women without CIN2+ lesions would be followed up by cytology every 12 months for two years. In the 3rd year of follow up, all women that were not biopsy proven CIN2+ would be called back and screened by cytology again. In follow-up period, women with ASC-US and above were referred to colposcopy and biopsied if clinically indicated. CIN2+ was the primary endpoint in analysis. The clinical performance and utility for risk stratification of DH3 HPV assay were assessed by SPSS 22.0 and SAS 9.4. Results Of 2180 qualified women, the prevalence of hr-HPV was 8.5% (185/2180), 45(2.1%) were HPV 16/18 positive. The clinical performance for HPV16/18 was 91.7% for sensitivity, 98.4% for specificity, respectively against CIN2+ detection at baseline. In four years of study, the corresponding rates of HPV 16/18 were 51.5% and 98.7%, respectively. The cumulative absolute risk for the development of CIN2+ was as high as 37.8% for HPV 16/18 positive women, followed by hr-HPV positive (14.6%), other hr-HPV positive (11.0%) and HPV negative (0.3%) in three years. The relative risk was 125.6 and 3.4 for HPV 16/18 positive group when compared with HPV negative and other hr-HPV positive group, respectively. Conclusions DH3 HPV assay demonstrated excellent clinical performance against CIN2+ detection in cervical cancer screening and utility of risk stratification by genotyping to promote scientific management of women with NILM cytology.